The Graffiti Writer as Homo Sacer: Writing, Liminality, and Sovereign Power in the Neo-Liberal City - Baldini, Andrea Lorenzo (Street Art & Urban Creativity, 2022)
Graffiti artists are frequently regarded as "liminal" figures, or people who exist on the outskirts of society. This paper looks at one aspect of their marginal status: legal liminality. I argue, using the work of the Italian philosopher Giorgio Agamben, that writers, like the homines sacri, live in a state of legal exception. As a result, they face uncontrollable violence and are denied fundamental rights. Though writers are subjected to abuse and intimidation, their particular circumstances also position them to challenge sovereign power in neoliberal cities. They can join a community without establishing an identity because of their ambiguous situation. As a result, they undermine the inclusion/exclusion dichotomy at the heart of biopolitics.